Digital Comic Media on Smartphones to Improve Communication Skills - Abd. Ghofur (Journal of Innovation in Educational and Cultural Research, 2022)
Communication skills in English are essential in global relations. The media get relevant and needed information. In practice, improving communication skills in English requires learning media as a tool. This study aims to develop digital comic media and their influence on improving communication skills. This research used a method with the gradual development of ADDIE: analysis, design, development, implementation, and evaluation. After being validated by media experts and material experts, the development results show that digital comic meets the criteria as media. In addition, the results of testing the application of digital comic media in learning English found that the communication skills were better by the increase in the ability to guess, arrange arguments, formulate definitions, and generalize. Applying digital comic media to improve communication skills can be a reference in learning English.